The Influence of Service Quality, Ease of Transaction and Transaction Security on Customer Satisfaction at PT Pegadaian UPC Adam Malik Medan City - Ruth Yoseline Sihombing; Clarita Surabina Br Purba; Grescilya Br Tarigan; Enda Noviyanti Simorangkir (International Journal of Scientific Multidisciplinary Research, 2024)
This At PT Pegadaian UPC Adam Malik in Medan City, research was done. Finding out how much Service Quality, Transaction Ease, and Transaction Security affect Customer Satisfaction at PT Pegadaian UPC Adam Malik Medan City was the aim of this study. This study employed a quantitative methodology, utilizing a sample of sixty questionnaires. SPSS was utilized to process the data. The study's findings suggest that service quality (X1) and customer happiness (Y) are significantly influenced by each other, at least in part (t-test). As the significance value of 0.043 is less than 0.05, it is evident that Ha is accepted and Ho is accepted. Partially (t-test), it was found that Ease of Transaction (X2) does not have a significant effect on Customer Satisfaction (Y). This is indicated by the acquired significant value (0.242 <0.05), indicating the rejection of Ho and the acceptance of Ha. It was discovered that Transaction Security (X3) and Customer Satisfaction (Y) are significantly impacted simultaneously (F-test). This is demonstrated by the significant value that was achieved (0.005 <0.05), indicating acceptance of both Ha and Ho